KEBIJAKAN PEMERINTAH DALAM MENINGKATKAN PENDAPATAN ASLI DESA (Studi Kasus: Desa Pacet Mojokerto): Studi Kasus: Desa Pacet Mojokerto - Faculty of Social; Political Sciences, Majapahit Islamic University, Mojokerto, Dian Wijaya; Faculty of Social; Political Sciences, Majapahit Islamic University, Mojokerto, Yuni Reza Sholikh; Faculty of Social; Political Sciences, Majapahit Islamic University, Mojokerto, Rachman Sidharta (Universitas Islam Majapahit, Indonesia, 2021)
This study aims to describe how the implementation of village government policies in increasing Original IncomePacet Village (PADes). Increasing village independence is closely related to the village's ability to manage Village Original Income (PADes).Pacet Village is a village dubbed as a tourist area of ??Pacet District, with its natural assets and potential that can beused as a field to improve the economy. The theory used in this study uses two studies, namely Talcott's AGIL TheoryParsons and the Concept of Public Policy. In this research, the method used is descriptive qualitative method. This data collection techniqueusing observation, interviews, and documentation. Based on the research, the writer can conclude that the success or failure ofThis increase in village original income cannot be separated from the role of the village government to properly manage the assets and potential of the village they ownhave. In addition, to increase economic growth and village performance for the Pacet BUMDES village, it can be measured from the results of the incoming budget fromvillage assets per year viewed from the short and medium term village government policies in advancing village performance for BUMDESThe village economy is also the key to the village's success in managing the village's potential. So in this case between the village governmentand the community contribute to each other in an effort to increase the village's original income.